Effect of biochar on soil properties on the Loess Plateau: Results from field experiments - Luo, Chaoyi; Yang, Jingjing; Chen, Wen; Han, Fengpeng (Geoderma, 2020)
•The soil bulk density is correlated with soil types and the biochar applied rates.•The soil organic carbon and total nitrogen increased after eight-year field study.•The soil NO3−–N is correlated with soil types and biochar application rates.•The effect of biochar application on NH4+–N and total phosphorus are very limited. Soil erosion on the Loess Plateau has been partly controlled, but soil nutrients remain limited throughout the region. Biochar amendments are an efficient method of improving availability of soil nutrients due to their strong adsorptive capacity; however, the effects of biochar amendments on different soil types on the Loess Plateau are not well understood. In this paper, we compared the effects of biochar on soil bulk density, soil organic carbon, and soil nitrogen and phosphorus contents among four soil types on the Loess Plateau. An eight-year field study was conducted in Loessal soil, Dark Loessial soil, Lou soil, and Aeolian sandy soil to investigate changes in soil bulk density and nutrient retention caused by biochar amendment at rates of 0 g/kg (control), 4 g/kg, 8 g/kg and 16 g/kg. Soil organic carbon, total nitrogen, total phosphorus, ammonium nitrogen, and nitrate nitrogen concentrations were measured eight years after biochar application. The biochar amendments significantly increased the soil organic carbon and nitrate nitrogen concentrations in the 0–40 cm layer of all soils. The nitrate nitrogen concentration in the Lou soil and Dark Loessial soil decreased with 4 g/kg biochar application and increased significantly with 8 g/kg and 16 g/kg biochar application, but it did not significantly change in the Loessal soil. In contrast, the nitrate nitrogen concentration in the Aeolian sandy soil decreased with increasing biochar application. Biochar amendments did not significantly influence soil ammonium nitrogen in the 0–20 cm soil layer. However, the soil phosphorus content in the 0–20 cm layer decreased with increasing biochar application, except in the Lou soil and Aeolian sandy soil. These data suggest that biochar-soil interactions on the Loess Plateau have the potential to enhance soil organic carbon and soil nitrogen storage. Moreover, using an appropriate biochar amendment rate according to soil type might help optimise the use of fertilizer on the Loess Plateau.